2013
DOI: 10.1021/jp4064998
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Electron Spectroscopy and Rotational Conformers of Group 6 Metal (Cr, Mo, and W) Bis(mesitylene) Sandwich Complexes

Abstract: Group 6 metal-bis(mesitylene) sandwich complexes are produced by interactions between the laser-vaporized metal atoms and mesitylene vapor in a pulsed molecular beam source, identified by photoionization time-of-flight mass spectrometry, and studied by pulsed-field ionization zero-electron kinetic energy spectroscopy and density functional theory calculations. Although transition metal-bis(arene) sandwich complexes may adopt eclipsed and staggered conformations, the group 6 metal-bis(mesitylene) complexes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In these calculations, we used the Becke’s three-parameter hybrid functional with the correlation functional of Lee, Yang, and Parr (B3LYP) and the 6-311+G­(d,p) basis set for C and H and the effective-core-potential SDD basis set for La. We have extensively used the DFT method and found it generally produced adequate results for the spectral and structural assignments of organometallic complexes. , No symmetry restrictions were imposed in the initial geometry optimizations, but appropriate point groups were used in the subsequent optimizations to help identify electronic symmetries. For each optimized stationary point, a vibrational analysis was performed to identify the nature of the stationary point (minimum or saddle point).…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…In these calculations, we used the Becke’s three-parameter hybrid functional with the correlation functional of Lee, Yang, and Parr (B3LYP) and the 6-311+G­(d,p) basis set for C and H and the effective-core-potential SDD basis set for La. We have extensively used the DFT method and found it generally produced adequate results for the spectral and structural assignments of organometallic complexes. , No symmetry restrictions were imposed in the initial geometry optimizations, but appropriate point groups were used in the subsequent optimizations to help identify electronic symmetries. For each optimized stationary point, a vibrational analysis was performed to identify the nature of the stationary point (minimum or saddle point).…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…The molecular structures of the neutral (doublet) and cationic (singlet) methylcobaltocene were optimized at the BPW91/ TZVP, B3PW91/6-311+G(d,p), B3PW91/6-311++G(d,p), B3LYP/ 6-311++G(d,p) and TPSSh/6-311+G(d,p) levels of DFT. These combinations of the GGA (BPW91) or hybrid (B3PW91) functionals and triple-z split valence basis sets have demonstrated earlier good performance when modelling the MATI spectra of bisarene complexes, [46][47][48][49][50][51][52][53][54][55][56][57][58] mixed sandwiches 59 and decamethylmanganocene. 45 The 10% exact exchange TPSSh meta-type functional 69 produced high-quality results for transition-metal systems.…”
Section: Computational Analysismentioning
confidence: 99%
“…DFT-supported MATI spectroscopy appeared to represent a powerful instrument for studying not only accurate ionization and vibrational energies of metallocenes, 28,45 bisarene complexes [46][47][48][49][50][51][52][53][54][55][56][57][58] or mixed sandwich systems 59 but also structural behaviors of these organometallics on ionization. 28,45,59 This opens new opportunities for investigations of substituent effects in sandwich compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Among metallocenes, the MATI spectrum has so far been recorded only for Cp 2 Co [ 52 ]. The MATI/ZEKE data have been obtained also for some bisarene complexes [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] and few mixed sandwiches [ 66 ]. These studies demonstrated new possibilities provided by the MATI and ZEKE techniques for detecting substituent effects and structural changes of sandwich molecules upon ionization [ 67 ].…”
Section: Introductionmentioning
confidence: 99%